2016
DOI: 10.4254/wjh.v8.i20.838
|View full text |Cite
|
Sign up to set email alerts
|

Lipogenesis in Huh7 cells is promoted by increasing the fructose: Glucose molar ratio

Abstract: AIM:To determine whether hepatocyte lipogenesis, in an in vitro cell culture model, is modulated by adjusting culture media monosaccharide content and concentration. METHODS:Hepatocytes (Huh7), demonstrating glucose and fructose uptake and lipid biosynthesis, were incubated in culture media containing either glucose alone (0.65-0.72 mmol/L) or isosmolar monosaccharide (0.72 mmol/L) comprising fructose:glucose (F:G) molar ratios ranging from 0.58-0.67. Following a 24-h incubation, cells were harvested and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, meta-analyses of studies with blood lipid and liver-related end points show no effect in trials that controlled for energy. 35 37 Studies in vitro also present conflicting conclusions: some studies showing differential effects of fructose at remarkably low (0.72 mM) concentrations of total monosaccharide with increasing fructose:glucose molar ratios; 38 other studies show no differential effects until higher (25 mM) doses of fructose were used. 39 Such concentrations are generally supra-physiological doses, being significantly higher than concentrations observed in portal blood, which rarely exceed 2 mM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, meta-analyses of studies with blood lipid and liver-related end points show no effect in trials that controlled for energy. 35 37 Studies in vitro also present conflicting conclusions: some studies showing differential effects of fructose at remarkably low (0.72 mM) concentrations of total monosaccharide with increasing fructose:glucose molar ratios; 38 other studies show no differential effects until higher (25 mM) doses of fructose were used. 39 Such concentrations are generally supra-physiological doses, being significantly higher than concentrations observed in portal blood, which rarely exceed 2 mM.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to human hepatocyte metabolism and function, these effects have yet to be clearly demonstrated. Using Huh7 cells, Windemuller et al (2016) provided evidence that increasing the molar ratio of fructose to glucose resulted in significant, dose-dependent increases in intracellular TAG; it is unclear if there were concomitant changes in the expression of relevant lipogenic genes as these were not measured. The more global metabolic effect of fructose on cellular metabolism has been explored by culturing HepG2 cells for 48 h in either glucose (5.5 or 10.5 mM) or a combination of glucose (5.5 mM) and fructose (5 mM) and collecting cells at 10 min, 1, 6 and 24 h after 48 h medium replacement (Meissen et al 2015).…”
Section: Summary Of In Vitro Hepatocyte and Adipocyte Cell Culture Stmentioning
confidence: 99%
“…Conditioned media from HepG2 cells treated with palmitate significantly increased alpha-SMA expression in LX-2 cells, although LX-2 cells directly treated with palmitate did not show the same response, suggesting that a secondary metabolite from palmitate-treated HepG2 cells was responsible for HSC activation [ 20 ]. Windemuller et al [ 26 ] showed that increasing the fructose to glucose ratio in Huh7 cells corresponded with elevated triacylglycerol and cholesterol synthesis, but this effect was not observed with increasing concentrations of glucose. In contrast, HepG2 cells treated with fructose did not show altered expression of lipogenic genes [ 22 ], although a combination of fructose, glucose, and fatty acids (palmitate and oleate) not only increased levels of triacylglycerols, total cholesterol, and inflammatory cytokines, but also upregulated expression of genes involved in carbohydrate and lipid metabolism [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated changes in intercellular metabolism resulting from exposure to these nutrients in primary or immortalized hepatocytes and hepatic stellate cells (HSCs) [20][21][22][23][24][25][26][27][28]. HSCs are quiescent under physiological conditions, but are activated to a myofibroblastic state in response to injurious stimuli, whereupon they begin to secrete cytokines and components of the extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%